First record of folivory in the tube-nosed fruit bat, Nyctimene rabori Heaney & Peterson, 1984 in Mt. Lantoy Key Biodiversity Area, Cebu, Philippines [Research note] - Alcazar, Steve Michael T.; Lillo, Edgardo P.; Nuevo, Ritche U.; Rosales, Raamah C.; Malaki, Archiebald Baltazar B. (2019)
Four individuals of Nyctimene rabori were captured at different bat net stations in Barangay Canbantug, Argao town within the peripheries of Mt. Lantoy Key Biodiversity Area in Cebu Island, Philippines at 500?700 meters above sea level. We present the first observation of folivory behavior in Nyctimene rabori on mango plant (Mangifera indica). The bat feed on young leaves and shoots of the mango plant where it was released. It chewed on the leaves, swallowing some parts and ejecting some. Interestingly, the bat also ate the petiole and the entire young green stem (about 6 in long and 0.5?0.8 cm diameter). It consumed the entire stem with only a small amount expelled. The activity lasted for almost 8 min of intermittent feeding. Fruit bat folivory is rarely documented in the Philippines. Knowledge on the diet of fruit bats is important in the conservation and management of the species. (Author's abstract)
Includes bibliographical references (pages 421-422)
Keywords: Biology; Folivory; Fruit bat; Mangifera indica; Mt. lantoy key biodiversity area; Nyctimene rabori